THE LATERAL THINKING PROCESSES IN SOLVING MATHEMATICAL WORD PROBLEMS REVIEWED AT ADVERSITY QUOTIENT AND REFLECTIVE COGNITIVE STYLE - Andi Saparuddin Nur; Kartono Kartono; Zaenuri Zaenuri; Rochmad Rochmad (IKIP Siliwangi and I-MES, 2022)
Solving word problems with a thought jump shows flexibility and the ability to use alternative procedures that are important for students to master. The thought jump is a feature of the lateral thinking process and is needed to overcome the various difficulties in solving mathematical word problems. However, lateral thinking has not been widely linked with adversity quotient and reflective cognitive style. This study aimed to describe students' lateral thinking processes in solving word problems in terms of adversity quotient and reflective cognitive style. This research is a qualitative descriptive study. The subjects in this study were junior high school students in Gowa Regency, South Sulawesi Province. The research instrument used the MFFT diagnostic test, ARP questionnaire sheet, word problem text, and interview guidelines. The results of this study indicate that climber-reflective subjects can think laterally and use them to solve the first and second-word problems well. Camper-reflective subjects can only think laterally for situations that are still within reach, while for more complicated cases, camper subjects are easily distracted and even stop solving problems. Quitter subjects solve word problems very procedurally, follow rigid algorithms, and cannot work backward when faced with difficulties.